Devising a framework of optogenetic coding in the auditory pathway: Insights from auditory midbrain recordings - Maria Michael; Bettina Julia Wolf; Astrid Klinge-Strahl; Marcus Jeschke; Tobias Moser; Alexander Dieter (Brain Stimulation, 2023)
Cochlear implants (CIs) restore activity in the deafened auditory system via electrical stimulation of the auditory nerve. As the spread of electric current in biological tissues is rather broad, the spectral information provided by electrical CIs is limited. Optogenetic stimulation of the auditory nerve has been suggested for artificial sound coding with improved spectral selectivity, as light can be conveniently confined in space. Yet, the foundations for optogenetic sound coding strategies remain to be established. Here, we parametrized stimulus-response-relationships of the auditory pathway in gerbils for optogenetic stimulation. Upon activation of the auditory pathway by waveguide-based optogenetic stimulation of the spiral ganglion, we recorded neuronal activity of the auditory midbrain, in which neural representations of spectral, temporal, and intensity information can be found. Screening a wide range of optical stimuli and taking the properties of optical CI emitters into account, we aimed to optimize stimulus paradigms for potent and energy-efficient activation of the auditory pathway. We report that efficient optogenetic coding builds on neural integration of millisecond stimuli built from microsecond light pulses, which optimally accommodate power-efficient laser diode operation. Moreover, we performed an activity-level-dependent comparison of optogenetic and acoustic stimulation in order to estimate the dynamic range and the maximal stimulation intensity amenable to single channel optogenetic sound encoding, and indicate that it complies well with speech comprehension in a typical conversation (65 dB). Our results provide a first framework for the development of coding strategies for future optogenetic hearing restoration.